The impact of photocatalytic Ag/TiO2 and Ag/N-TiO2 nanoparticles on human keratinocytes and epithelial lung cells. (15th March 2019) - Rebleanu, Daniela; Gaidau, Carmen; Voicu, Geanina; Constantinescu, Cristina Ana; Mansilla Sánchez, Catalina; Rojas, Teresa Cristina; Carvalho, Sandra; Calin, Manuela
Abstract: The potential human health risks following the exposure to inorganic nanoparticles (NPs) is a very important issue for their application in leather finishing industry. The aim of our study was to investigate the cytotoxic effect of silver (Ag)/titanium dioxide (TiO2 ) NPs on human cells. Photocatalytic NPs were prepared by electrochemical deposition of Ag on the surface of TiO2 and nitrogen (N)-TiO2 NPs and, subsequently, physico-chemical characterized. Then, a set of experiments have been performed to study the cytotoxicity and cell death mechanisms involved, the changes in cell morphology and the production of ROS induced in human keratinocytes (HaCaT) and human lung epithelial cells (A549) by exposure to NPs. Moreover, the changes in major signaling pathways and the inflammatory response induced by Ag/N-TiO2 NPs in A549 cells were investigated. The data showed that cell death by late apoptosis/necrosis is induced in cells as function of the dose and the type of NPs and is characterized by morphological changes and cytoskeletal disorganization and an increase in reactive oxygen species (ROS) production. The exposure of A549 cells to Ag/N-TiO2 NPs determine the activation of ERK1/2 MAP-kinase pathway and the release of pro-inflammatory mediators CXCL1, GM-CSF and MIF, known to be involved in the recruitment of circulating neutrophils and monocytes.